2009
DOI: 10.1128/aac.00397-09
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polymorphisms of Human Immunodeficiency Virus Type 1 Integrase and Inherent Susceptibilities to a Panel of Integrase Inhibitors

Abstract: We evaluated the human immunodeficiency virus type 1 (HIV-1) integrase coding region of the pol gene for the presence of natural polymorphisms in patients during early infection (AHI) and with triple-class drugresistant HIV-1 (MDR). We analyzed selected recombinant viruses containing patient-derived HIV-1 integrase for susceptibility to a panel of strand transfer integrase inhibitors (InSTI). A pretreatment sequence analysis of the integrase coding region was performed for 112 patients identified during acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
78
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 38 publications
8
78
0
1
Order By: Relevance
“…M50I and D288E are natural polymorphisms detected in clinical isolates (http://hivdb.stanford.edu/, Stanford University HIV drug resistance database). V151I is a polymorphic sub-stitution that has been selected by several INSTIs, without having significant effects on RAL and EVG susceptibility (28,36,42,43). H51Y is an E92Q-linked secondary mutation selected in the presence of EVG in vitro and in patients (43,60).…”
Section: Discussionmentioning
confidence: 99%
“…M50I and D288E are natural polymorphisms detected in clinical isolates (http://hivdb.stanford.edu/, Stanford University HIV drug resistance database). V151I is a polymorphic sub-stitution that has been selected by several INSTIs, without having significant effects on RAL and EVG susceptibility (28,36,42,43). H51Y is an E92Q-linked secondary mutation selected in the presence of EVG in vitro and in patients (43,60).…”
Section: Discussionmentioning
confidence: 99%
“…All mutant proviral clones were verified by DNA sequence analysis of the entire XbaI/SacII recombinant joint. Wild-type and mutant XbaI/SacII inserts were also reconstructed into pR7/3(X/S)Bsd (52,70), an env Ϫ proviral derivative in which the amino terminus of nef is replaced with bsd, a gene conferring resistance to the microbial antibiotic blasticidin S. Single-step infectious, vesicular stomatitis virus glycoprotein (VSV-G)-pseudotyped viral stocks were prepared by cotransfection of the pR7/3(X/S)Bsd variants with pCI-VSV-G, a VSV-G expression vector.…”
Section: Methodsmentioning
confidence: 99%
“…Primary RAL resistance mutations confer changes in the IN coding region at amino acid positions 143, 148, and 155 (4). Additional resistance mutations resulting in amino acid substitutions V72I, L74I or L74M, E92Q, T97A, F121Y, E138K, G140S or G140A, V151I, E157Q, G163R, I203M, and S230R have also been described (D. Cooper and B. Nguyen, presented at the 14th Conference on Retroviruses and Opportunistic Infections, Los Angeles, CA, 25 to 28 February 2007) (19,21). Recent studies have reported that the primary resistance mutations N155H and Q148R, Q148H, or Q148K represent mutually exclusive and nonoverlapping pathways (8,20).…”
mentioning
confidence: 99%